Training on Accurate Software Application for Employees of PT. ASSA Logistics: Enhancing Financial Operational Efficiency through Digital Literacy - Cici Handayani; Sharina Amanda; Widy Hastuty; Hermansyah; Zakia Fadilla (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity addresses the low digital accounting literacy among employees of PT. ASSA Logistics, a growing logistics company in Medan. The manual bookkeeping system previously used led to frequent errors, delayed financial reporting, and inefficient operational workflows. This program aimed to enhance the participants' competencies in using Accurate accounting software through structured participatory training. The method applied was Community-Based Participatory Training (CBPT), combining workshops, hands-on simulations, and mentoring sessions involving 25 employees from finance, inventory, and administration divisions. The training was conducted on November 14, 2025, at the company's head office in Medan. Evaluation through pre-test and post-test showed a significant increase in participants' comprehension and practical skills, with an average score improvement of 42%. Furthermore, participants reported increased confidence in managing daily transactions, generating financial statements, and utilizing inventory modules. This activity not only improved individual competencies but also supported the company's digital transformation goals, contributing to better accuracy, efficiency, and decision-making processes. The success of this program highlights the importance of tailored digital training for SMEs in the logistics sector to enhance competitiveness and operational sustainability